2011
DOI: 10.1002/dev.20533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social conditions during early development on stress response and personality traits in great tits (Parus major)

Abstract: Environmental conditions during early development play a crucial role in shaping an organism's phenotype. To test how social group size affects stress response and behavioral characteristics, we used great tits (Parus major) from selection lines for exploratory behavior, a proxy for an avian personality trait, and birds from the wild in a brood size manipulation experiment. Nestlings were tested for stress response using an established stress test and after independence subjects were tested for exploratory beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 63 publications
1
45
0
Order By: Relevance
“…More specifically, based on previous work on sticklebacks and other animals, we predicted neophobia would decrease for fish raised with increased simulated predator stress, habitat complexity, or social stress [e.g., Elvidge et al, 2016;Christensen and Nielsen, 2004;Naguib et al, 2011;Bannier et al, 2017]. We found that fish raised in complex physical or socially stressful environments were less neophobic, confirming our predictions and matching findings also in birds [Christensen and Nielsen, 2004].…”
Section: Early Environment and Behaviorsupporting
confidence: 79%
See 3 more Smart Citations
“…More specifically, based on previous work on sticklebacks and other animals, we predicted neophobia would decrease for fish raised with increased simulated predator stress, habitat complexity, or social stress [e.g., Elvidge et al, 2016;Christensen and Nielsen, 2004;Naguib et al, 2011;Bannier et al, 2017]. We found that fish raised in complex physical or socially stressful environments were less neophobic, confirming our predictions and matching findings also in birds [Christensen and Nielsen, 2004].…”
Section: Early Environment and Behaviorsupporting
confidence: 79%
“…DOI: 10.1159/000489942 Lima and Dill, 1990;Bell and Sih, 2007;Naguib et al, 2011;Taborsky and Oliveira, 2012]. We found that fish raised in complex physical environments were more aggressive, and fish in our other early environmental treatments did not differ in aggression relative to control fish.…”
Section: Early Environment and Behaviormentioning
confidence: 49%
See 2 more Smart Citations
“…Dimitsantos et al, 2007). Surely, we cannot rule out that potential epigenetic or neuroendocrine correlates of early life conditions, in particular of sibling number or litter size, might also be involved in shaping the behavioral development of the young (Champagne, 2008;Koolhaas et al, 1999;Koolhaas, de Boer, Coppens, & Buwalda, 2010;Naguib, Flörcke, & van Oers, 2011;Rödel et al, 2010;Sachser et al, 2011;Siegeler, Sachser, & Kaiser, 2011). However, due to the strong effects of starting body mass-overriding the effects of litter size-we suggest that the individual body mass and size directly and causally affect the ontogeny of personality traits.…”
Section: Developmental Psychobiologymentioning
confidence: 70%